2018
DOI: 10.2136/sssaj2018.01.0007
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Soil Crack Volume at the Pedon Scale using Available Soil Data

Abstract: Core Ideas Desiccation cracks make runoff and infiltration predictions difficult in expansive soils. A crack‐volume model based on water content and soil properties was developed. Crack volume was measured in situ using digital photography of excavated soil layers. The new model improved crack volume estimates over a model based on layer thickness. A critical gap in hydrology knowledge is predicting the partition of runoff and infiltration during rainfall events in shrink‐swell soils with desiccation cracks. K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Even though it comes at the cost of two extra parameters (ϒ and K interaggr,max ), the results here indicate that including both interaggregate and interblock cracks can facilitate simulations from the smaller soil matrix scale to the larger hillslope scale. Beyond the studies examined here, such differentiation of crack domains may also reconcile observed and modeled crack distributions, such as have been measured in laboratory (Chertkov & Ravina, 2002) and field settings (Bagnall, 2014;Neely et al, 2018).…”
Section: Water Resources Researchsupporting
confidence: 72%
“…Even though it comes at the cost of two extra parameters (ϒ and K interaggr,max ), the results here indicate that including both interaggregate and interblock cracks can facilitate simulations from the smaller soil matrix scale to the larger hillslope scale. Beyond the studies examined here, such differentiation of crack domains may also reconcile observed and modeled crack distributions, such as have been measured in laboratory (Chertkov & Ravina, 2002) and field settings (Bagnall, 2014;Neely et al, 2018).…”
Section: Water Resources Researchsupporting
confidence: 72%
“…The wetting event in Fig. 4A occurred when soil VWC was relatively moist, and we expect no cracks were open, above 0.35 m 3 m −3 (Neely et al, 2018). After 25 mm of rain, the soil profile wet quickly at depth and simulations agree more closely with measurements when PALMS M&M is used.…”
Section: Resultsmentioning
confidence: 91%
“…The M&M module's nine parameters were chosen based on the official series description of a Burleson clay (National Cooperative Soil Survey, 2018) as interpreted by the National Soil Survey Center (2002), with the exception of the COLE value, which was measured as 0.17 m m −1 by a previous study at this location (Neely et al, 2018). The saturated hydraulic conductivity of the ped (K s,ped ) was assigned the Rawls et al (1992) look-up table value of 0.06 cm h −1 .…”
Section: Palms Pedon-scale Simulationsmentioning
confidence: 99%
“…Comparison of the percentage of area occupied by cracks measured at the site by Neely et al (2018) to the percentage of area of the neutron moisture meter (NMM) measurement volume that was occupied by large‐ and small‐annulus voids used in this experiment. The NMM measurement volume was dependent on soil water content and was calculated using Eq.…”
Section: Methodsmentioning
confidence: 99%
“…[1]. Error bars for measured crack area are standard deviations of areal crack volume around four access tubes (Neely et al 2018). Error bars for annuli are the standard deviations from five small and six large annuli measurements.…”
Section: Methodsmentioning
confidence: 99%